Tinjauan Pustaka AKURASI PEMERIKSAAN LFA CRYPTOCOCCAL ANTIGEN SERUM DIBANDINGKAN DENGAN KULTUR DALAM PENEGAKAN DIAGNOSIS MENINGITIS KRIPTOKOKUS - Dimas Seto Prasetyo; Janice Tandraeline; Maria Astika Dewi; Nadia Maretti (PERDOSNI, 2021)
Cryptococcosis is an infection caused by Cryptococcus, with the main pathogen is Cryptococcus neoformans. This mainly infects immunocompromised patient, e.g people living with HIV/AIDS. The gold standard for diagnosis is culturing from cerebrospinal fluid but this technique is time-consuming. Besides that, few centers have resources (e.g neurologist) to perform lumbar puncture and patients may have certain contraindication for lumbar puncture, e.g elevated intracranial pressure. There will be a need of simple and less invasive diagnostic method, such as cryptococcal antigen detection using lateral flow assay. The objective of this evidence-based case report is to compare the cryptococcal antigen lateral flow assay from serum in establishing cryptococcal meningitis with conventional culture method from cerebrospinal fluid. Method: Article searching was conducted in Pubmed database (MEDLINE), Embase, and Wiley Online Library. Article screening was done by 3 researcher, using inclusion and exclusion criteria, and examination of article completeness. The full article was also examined for answering the clinical question. Result: From the literature research, we found 2 articles from the database and 1 systematic review from Googlescholar which fulfilled eligibility criteria. The 2 articles were already included in the systematic review so the critical review was only conducted to the systematic review article. The report showed that the cryptococcal antigen detection using lateral flow assay from serum yielded a relatively high sensitivity and specificity (97,9% and 89,5% respectively) Conclusion: The accuracy of cryptococcal antigen detection from serum using LFA in establishing cryptococcal meningitis in HIV patient was comparable to conventional cerebrospinal fluid culture. Keywords: cyrptococcal meningitis, lateral flow assay